CULTURE OF UZBEK NATION (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Culture of Uzbekistan is one of the brightest and original cultures of East. For example, it is inimitable national music, dances and painting, unique national kitchen and clothes.The Uzbek national clothes of the end of XX centuries remain constant up these days.Uzbek cuisine is one of the most colorful of Oriental Cuisines.This article information about Culture of Uzbekistan.